Giovanna Casagrande: Gola e Preghiera nella clausura dell' ultimo '500 - Riley, Gillian (Petits Propos Culinaires, 1990)
Giovanna Casagrande: Gola e Preghiera nella clausura dell' ultimo '500, with a modern Italian version and notes by Giovanni Moretti and glossary, indices and an editorial note by Maria Raffaella Trabalza: Edizioni dell' Arquata, via Nazario Sauro 21, Foligno 05034, Perugia: 400 pp, 64 line illustrations, 2 half-tones, handsome card cover, 60,000 lire.